NILAI-NILAI PENDIDIKAN ISLAM DALAM TAREKAT QADIRIYAH - Ischak Suryo Nugroho (IAIN Purwokerto, 2019)
Islamic education is not only focussed on physical problems such as cognitive but also on spiritualilty which the mind’s ability that is build in tasawuf by tarekat way. Qadiriyah is a taken from the name of its founder Abd. Al-Qadir Jilani who is popular with Syekh Abd. Al-Qadir Jilani Al-Ghawsts atau Quthb Auliya. Syeikh Abd. Al-Qadir is athe founder of spiritual which is masive and organized well. Before Syeikh Abd. Al-Qadir Jilani, Islamic spiritual is individual and not well-organized. According to Al Sya’rani, the form and characteristic of Tarekat Syaikh Abd. Al-Qadir is tauhid . The way to achieve the syariat is by spritual and mental activities. The Syaikh Abd. Al-Qadir Al-Jilani always emphasizes on purificstion from the men’s desire. Some of the lessons are taubat, zuhud, tawakal, syukur, ridha and honest. Key Words : Islamic Education, Tarekat, Qadiriyah